¿Cómo debería un historiador leer las fuentes escritas de los siglos XVI y XVII en quechua o en castellano basadas en informantes quechuahablantes? (J.S.) - Szemiński, Jan; Andrade Ciudad, Luis; Pärssinen, Martti H. (Pontificia Universidad Católica del Perú, 2024)
Historians studying the pre-Inca era, the Inca Empire, and the colonial period often do not know Quechua and are unaware of the importance of knowing the language. This article will show, through a series of examples, the problems that can arise from this lack of knowledge. Each example illustrates a problem and offers a suggestion for resolving it.

Los historiadores que estudian las épocas preincas, el Imperio inca y el periodo colonial, en muchos casos, no saben quechua ni se dan cuenta de la importancia del conocimiento de esta lengua. En esta nota, se mostrará a través de una serie de ejemplos los problemas que pueden surgir a causa de este desconocimiento. Cada ejemplo ilustra un problema y ofrece una sugerencia sobre cómo resolverlo.
How should a historian read 16th and 17th century written sources in Quechua or Spanish which are based on Quechua-speaking informants?
Keywords: Quechua; Aymara; Pan-Andean vocabulary; Colonial documentary sources; Incas; Etymology; Ethnohistory; Quechua; Aymara; Vocabulario panandino; Fuentes documentales coloniales; Incas; Etimología; Etnohistoria; https://purl.org/pe-repo/ocde/ford#6.01.01